Marine macroalgae as sources of protein and bioactive compounds in feed for monogastric animals - Øverland, Margareth (J Sci Food Agric, 2018)
Marine macroalgae are considered as promising sustainable alternatives to conventional terrestrial animal feed resources. The advantages include high growth rate, potential cultivation in saltwater, and no occupation of arable land. Macroalgae are broadly classified as brown (Phaeophyta), red (Rhodophyta) and green (Chlorophyta) algae, and are a diverse group of marine organisms. The nutritional value of macroalgae is highly variable. The protein and essential amino acid content can be low, especially in brown species, and indigestible polysaccharides adversely affect the energy value. Optimal use of macroalgae in feeds requires suitable processing, and biorefinery approaches may increase protein content and improve nutrient availability. Macroalgae are rich in unique bioactive components and there is a growing interest in the potentially beneficial health effects of compounds such as laminarin and fucoidan in different macroalgal and macroalgal products. This review summarizes current literature on different aspects of the use of macroalgae as sources of protein and health‐promoting bioactive compounds in feed for monogastric animal species. © 2018 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.